Prediction of state anxiety in athletes based on personality traits - Zubić Ivana M. (Fizička Kultura, 2021)
The goal of this research was to test whether and to what extent personality traits contribute to the explanation of state anxiety in athletes. This study relied on a multidimensional construct of anxiety which includes somatic and cognitive anxiety and sport self-confidence. Dimensions of anxiety were measured with "Competitive State Anxiety Inventory-2"-CSAI-2, and HEXACO basic personality traits were measured with the instrument HEXACO-60. The research sample consisted of 117 athletes, who were engaged in various competitive sports. Results showed the statistically significant correlations between honesty, emotionality, extraversion, and conscientiousness as personality traits on the one hand and cognitive anxiety, somatic anxiety and self-confidence on the other. Whereas correlations between agreeableness and openness to experience on the one hand and cognitive anxiety, somatic anxiety and self-confidence on the other are not statistically significant. Multiple regression analysis were conducted with the aim of predicting the dimensions of anxiety based on personality traits in athletes. Based on personality traits 37% of variability in cognitive anxiety, 30% of somatic anxiety, and 36% of variability in self-confidence were explained. This study provided a better understanding of the personality traits of athletes that contribute to state of anxiety, coping with challenges and reacting in competitive situations.